Location of urban logistics distribution centers considering cargo transportation services of a public transportation system - Wang, Qian; Zheng, Jianfeng; Liu, Huibin; Wang, Yao; Li, Xia (Transport, 2025)
Urban logistics distribution accounts for a large proportion of CO2 emissions generated by urban transportation. Reducing CO2 emissions in the process of logistics distribution is one of the urgent urban problems to be solved. This article investigates the location of urban logistics distribution centers considering cargo transportation services of a public transportation system. Considering one or several bus lines for representing a public transportation system, several collaborative distribution scenarios are studied, and 2 mixed integer linear programming models are established to explore the impact of the public transportation system on the location of distribution centers in urban logistics. Numerical experiments show the influence of different bus lines on the location of distribution centers, collaborative distribution and truck carbon emissions in Dalian (China). In any case, the possibility of establishing distribution centers in blocks 5 and 42 of Dalian is very high. When bus lines are used, the highest bus line utilization can reach 47.83%, and the CO2 emission can be reduced by up to 36.3%. In terms of different bus lines, line 2002 is more suitable to participate in the collaborative distribution in Dalian compared with other bus lines. First published online 2 February 2026